Citizenship, Belonging, and Political Community in Africa Dialogues between Past and Present - Hunter, Emma (Ohio University Press, 2016)
Africa, it is often said, is suffering from a crisis of citizenship. At the heart of the contemporary debates this apparent crisis has provoked lie dynamic relations between the present and the past, between political theory and political practice, and between legal categories and lived experience. Yet studies of citizenship in Africa have often tended to foreshorten historical time and privilege the present at the expense of the deeper past.Citizenship, Belonging, and Political Community in Africa provides a critical reflection on citizenship in Africa by bringing together scholars working with very different case studies and with very different understandings of what is meant by citizenship. By bringing historians and social scientists into dialogue within the same volume, it argues that a revised reading of the past can offer powerful new perspectives on the present, in ways that might also indicate new paths for the future.The project collects the works of up-and-coming and established scholars from around the globe. Presenting case studies from such wide-ranging countries as Sudan, Mauritius, South Africa, Côte d'Ivoire, and Ethiopia, the essays delve into the many facets of citizenship and agency as they have been expressed in the colonial and postcolonial eras. In so doing, they engage in exciting ways with the watershed book in the field, Mahmood Mamdani's Citizen and Subject.Contributors: Samantha Balaton-Chrimes, Frederick Cooper, Solomon M. Gofie, V. Adefemi Isumonah, Cherry Leonardi, John Lonsdale, Eghosa E.Osaghae, Ramola Ramtohul, Aidan Russell, Nicole Ulrich, Chris Vaughan, and Henri-Michel Yéré.